Two novel polyvalent phages: a promising approach for cross-order pathogen control in aquaculture - Chengcheng Li; Yufei Yue; Rui Yin; Jiulong Zhao; Zengmeng Wang; Shailesh Nair; Yongyu Zhang (Virology Journal)
Abstract Bacteriophages represent a promising alternative to antibiotics for controlling bacterial pathogens. However, phage application is often hindered by its narrow host range in preventing diseases caused by multiple unknown pathogens. While broad-host-range phages capable of cross-genus or cross-order infections, offer significant advantages in addressing this challenge, they are rarely isolated. In this study, we isolated two polyvalent lytic phages, SA-P and SA-M, through a multi-host enrichment strategy. These phages exhibited remarkable cross-order infectivity against the co-occurring aquaculture pathogens Shewanella algae and multiple Vibrio species. We confirmed that SA-P executes a complete lytic cycle in these cross-order hosts, indicating exceptional compatibility of its lysis systems across taxonomic orders. Genomic analysis revealed that their broad host recognition ability may stem from their diverse tail fiber and tailspike proteins. Notably, SA-P and SA-M are the first phages reported to infect S. algae, and their combined application exhibited a sustained suppression of pathogen growth. Proteomic phylogenetic analysis suggests these phages represent a novel unclassified viral genus and family, respectively. This study provides two promising polyvalent phages and their cocktails as potential solution for cross-order pathogen control in aquaculture.